Moses, Elijah, and Jesus: Reflections on the basic structures of the Bible - Abraham van de Beek (In die Skriflig, 2012)
This article deals with the end of the lives of Moses and Elijah as the representatives of the Torah and the Prophets. Moses was not allowed to enter the Promised Land, and Elijah left it before he was taken up. These events are interpreted as indicating that the Law is not able to bring the people into the Promised Land and that the Prophets cannot keep them there. The end of Moses’ life is also the end of the Torah. The Prophets end with the call for a new Elijah. The Ketubim, as the human response on God’s acting, do not better. The Hebrew Bible ends with the exile. The New Testament begins where the Prophets end: a new Elijah, in the person of John the Baptist. He works at exactly the place where Israel entered the land after Moses’ death and where Elijah left the land. It is a reprise of the fulfilment of the promise. John points to Jesus, who begins his work at this place, not going on dry feet through the Jordan River,but fulfilling all righteousness when drawn into the water of God’s judgement. Then the way to the land is open to Moses and Elijah in the glory of God on the Mount of Transfiguration, when they speak about the exodus of Jesus on the cross. Salvation is not in the law or in conversion but in being baptised into Christ in his death.